"Los Mártires" de la modernización en Bogotá: escenarios de la memoria a través de la rutina y el abandono (2020)
The analysis and project process is located in the 14th locality of Bogotá D.C., capital of the Colombian country, called Los Martires. One of the most important events, undoubtedly, was the opening of the Sabana Station, which in 1917 made the town one of the most crucial of the capital, due to the great urban development that finally made Bogota a capital city, but above all a modern capital of the South American continent. Despite this, modernity has not been very successful, especially in Colombia, and the closure of the station itself soon generated a wave contrary to the aforementioned. The sector, in fact, with the end of the operations of the national railroads was progressively abandoned by part of the population, constituting today a part of the historic center of the city apparently without any historical or sociological value. The analysis made has tried to demonstrate, through the focus on some specific architectural elements identified, such as the stratifications of time, that the locality has fallen into oblivion precisely because of these events of social degradation, After the closure of fundamental poles of the sector, as was that of the Savannah Station. These stratigraphies have guided the whole process to understand that the main topic of this thesis would be that of memory. The memory of traces of the past that today are totally forgotten by the indifference of the citizens themselves. The project tries to respond in a timely manner to dynamic backdrops, trying to return to the locality its former splendor, but above all to manifest a reality, not only Colombian but Latin American, so the historic centres are completely abandoned and invaded by rubble and ruins.